Pathogenecity of Yersinia enterocolitica for mice. - Carter, P B (1975)
A laboratory infection of Yersinia enterocolitica in mice which closely resembles the naturally acquired human infection is described Intravenous inoculation of mice with small numbers of Y. enterocolitica gives rise to a systemic, pyogenic infection involving primarily the spleen, liver, and lungs. Massive neutrophil infiltration of these organs occurs early in the infection, eventually leading to large abscesses and pulmonary consolidation. Mice infected intragastrically show neutophil infiltration in the Peyer's patches of the distal ileum less than 24h postinfection. The Peyer's patches are unable to contain the infection which spreads to the mesenteric lymph node, causing large abscesses in the medullary regions. Soon after, the infection becomes systemic with abscesses forming in the liver, spleen, and lungs, and the total peripheral leukocyte count rises dramatically to over 30,000/mm2. A serological response, in the form of agglutinating antibody, begins to appear 2 weeks after infection. Possible causes of death and the usefulness of this infectious disease model are discussed.